FAKTOR MOTIVASI, MINAT GURU, DAN PENDAPATAN ORANG TUA KAITANNYA TERHADAP HASIL BELAJAR SISWA - Devie Christina P., (Pendidikan Ekonomi, 2011)
This study aimed to determine whether students motivation factor, the interest of students, teachers and parents income affect student learning outcomes in economic subject, and what the dominant factor affects student learning outcomes in economic subject. The data were collected with questionnaires and report cards. The study used multiple regressions. The study showed that motivation and interest of students, teachers, and parents income affected significantly the students learning outcomes. Motivation is the most dominant variable which affected the students learning outcome.